Measurement of diets that are healthy, environmentally sustainable, affordable, and equitable: A scoping review of metrics, findings, and research gaps - Webb, Patrick; Livingston Staffier, Kara; Lee, Hyomin; Howell, Brian; Battaglia, Kyra; Bell, Brooke M.; Matteson, Julia; McKeown, Nicola M.; Cash, Sean B.; Zhang, Fang Fang; Decker Sparks, Jessica L.; Blackstone, Nicole Tichenor (Frontiers in Nutrition, 2023)
Research on the impacts of dietary patterns on human and planetary health is a rapidly growing field. A wide range of metrics, datasets, and analytical techniques has been used to explore the role of dietary choices/constraints in driving greenhouse gas (GHG) emissions, environmental degradation, health and disease outcomes, and the affordability of food baskets. Many argue that each domain is important, but few have tackled all simultaneously in analyzing diet-outcome relationships. This paper reviews studies published between January 2015 and December 2021 (inclusive) that examined dietary patterns in relation to at least two of the following four thematic pillars: i) planetary health, (including, climate change, environmental quality, and natural resource impacts), ii) human health and disease, iii) diet cost/affordability economic outcomes, including diet cost/affordability and iv) social justice outcomes, (e.g., wages, working conditions), conditions, and culturally-relevant diets equity, and disparities, including ( racial, economic, etc. other). We systematically screened 2,425 publications by title and abstract and included data from 42 eligible publications in this review. The most common domain pairing was diet with environmental impacts (specifically climate change), followed by health impacts. Most dietary patterns used were statistically estimated or simulated rather than observed. A rising number of studies consider the cost/affordability of dietary scenarios in relation to optimized environmental and health outcomes. However, only six publications incorporate social justice parameterssustainability outcomes, which represents an under-explored dimension of food system concerns. This review suggest a need for i) transparency and clarity in datasets used and analytical methods; ii) explicit integration of indicators and metrics linking social justice and economic issues to the commonly-assessed diet-climate-planetary ecology relationships; iii) inclusion of data and researchers from low- and middle-income countries; iv) inclusion of processed food products to reflect the reality of consumer choices globally; and v) attention to the implications of findings for policymakers. Better understanding is urgently needed on dietary impacts on all relevant human and planetary domains simultaneously.